2022
DOI: 10.1051/e3sconf/202234005005
|View full text |Cite
|
Sign up to set email alerts
|

Economic fluctuations and monetary policy on the stock market during the COVID-19 pandemic in Indonesia

Abstract: The purpose of this study is to examine the stock market’s resiliency in the face of economic fluctuations and a crisis caused by the COVID-19 outbreak. using monthly data from 2011 to 2020 and an error correction model with the Composite Stock Price Index (conventional stock market system) and the Jakarta Islamic Index (Islamic stock market system) as dependent variables and policy interest rates, exchange rates, inflation, and crises as independent variables. In both stock market models, the regression resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Studies have found that inflation rates can affect the returns of both Islamic and conventional stock markets, with some research indicating a positive long-term relationship between inflation and stock market returns (Jelilov, Iorember, Usman, & Yua, 2020;Kwofie & Ansah, 2018). However, other studies suggest that inflation may have a negative impact on the Sharia Stock Market index in the short term, especially during economic shocks such as the COVID-19 pandemic (Halim, 2020;Suriani, Nasir, & Ernawati, 2022).…”
Section: Inflation and Sharia Stock Marketmentioning
confidence: 99%
“…Studies have found that inflation rates can affect the returns of both Islamic and conventional stock markets, with some research indicating a positive long-term relationship between inflation and stock market returns (Jelilov, Iorember, Usman, & Yua, 2020;Kwofie & Ansah, 2018). However, other studies suggest that inflation may have a negative impact on the Sharia Stock Market index in the short term, especially during economic shocks such as the COVID-19 pandemic (Halim, 2020;Suriani, Nasir, & Ernawati, 2022).…”
Section: Inflation and Sharia Stock Marketmentioning
confidence: 99%